2019
DOI: 10.1080/10408444.2019.1578730
|View full text |Cite
|
Sign up to set email alerts
|

Hexavalent chromium and stomach cancer: a systematic review and meta-analysis

Abstract: Hexavalent chromium [Cr(VI)] is known to cause lung cancer in workers of certain industries, but an association with stomach cancer is uncertain and widely debated. Systematic review and meta-analyses were conducted to assess the risk of stomach cancer mortality/morbidity in humans and experimental animals exposed to Cr(VI). In accordance with the protocol (PROSPERO #CRD4201605162), searches in PubMed and Embase V R , and reviews of secondary literature bibliographies, were used to identify eligible studies. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(21 citation statements)
references
References 69 publications
0
17
0
4
Order By: Relevance
“…In addition, there is a great deal of the relative health effects of the various routes of exposure for Cr (VI) [16]. Occupational exposure to Cr (VI) by inhalation depends upon the job function and industry, but can reach several hundred micrograms per cubic meter and it is associated with lung cancer [1,62,90,97]. Chronic inhalation exposure to hexavalent chromium results in effects on the respiratory tract, damaging the nasal septum with perforations and ulcerations, causing bronchitis, decreasing in lung function, pneumonia, and nasal itching and soreness [98].…”
Section: Health Riskmentioning
confidence: 99%
“…In addition, there is a great deal of the relative health effects of the various routes of exposure for Cr (VI) [16]. Occupational exposure to Cr (VI) by inhalation depends upon the job function and industry, but can reach several hundred micrograms per cubic meter and it is associated with lung cancer [1,62,90,97]. Chronic inhalation exposure to hexavalent chromium results in effects on the respiratory tract, damaging the nasal septum with perforations and ulcerations, causing bronchitis, decreasing in lung function, pneumonia, and nasal itching and soreness [98].…”
Section: Health Riskmentioning
confidence: 99%
“…The risk of cancer with exposure to occupational hexavalaent Cr (Cr(VI)) was studied more than 100 years ago [88]. Workers in certains industries such as chromate production, pigment production, and chrome plating have a significant greater increase in the risk for developing lung cancer [89].…”
Section: Chromium (Cr)mentioning
confidence: 99%
“…Furthemore, Cr(VI) is classified as a known human carcinogen by the International Agency for Research on Cancer, known for causing cancer of the lung and positive associations with cancer of the nose and nasal sinuses [90]. However, conflicting evidence and analysis have been provided for stomach or other cancers, but a recent analysis reported that Cr(VI) does not pose a stomach cancer hazard in human beings [88]. Although Cr(III) may not have been reported to be toxic, when it oxidizes to Cr(VI), it is toxic [91].…”
Section: Chromium (Cr)mentioning
confidence: 99%
“…El cromo presenta cinco estados de valencia, de los cuales los más importantes y estables en medios naturales son el cromo (III) y (VI), que se encuentran presentes en acuíferos naturales y aguas residuales (Cheung y Ji 2007, Dhal et al 2013, Evelyne y Ravisanka 2014, Tommasi y Lombardelli 2017. El Cr(VI) es considerado un agente mutagénico, carcinogénico y teratogénico, el cual se presenta como cromato o dicromato, dependiendo del pH en donde se encuentre (Dhal et al 2013, Suh et al 2019. Debido a su naturaleza química, no puede degradarse, sólo transformarse a una forma menos tóxica como es el Cr(III), el cual es esencial para el metabolismo humano en bajas concentraciones, ya que participa en el metabolismo de la glucosa, el colesterol y los ácidos grasos, donde desempeña un papel importante en diferentes reacciones enzimáticas (Arderiu 1998, Watson y Logan 2011, Dhal et al 2013, Suh et al 2019.…”
Section: Introductionunclassified
“…El Cr(VI) es considerado un agente mutagénico, carcinogénico y teratogénico, el cual se presenta como cromato o dicromato, dependiendo del pH en donde se encuentre (Dhal et al 2013, Suh et al 2019. Debido a su naturaleza química, no puede degradarse, sólo transformarse a una forma menos tóxica como es el Cr(III), el cual es esencial para el metabolismo humano en bajas concentraciones, ya que participa en el metabolismo de la glucosa, el colesterol y los ácidos grasos, donde desempeña un papel importante en diferentes reacciones enzimáticas (Arderiu 1998, Watson y Logan 2011, Dhal et al 2013, Suh et al 2019. El Cr(III) considerado 100 veces menos tóxico y 1000 veces menos mutagénico que el Cr(VI) (Dhal et al 2013, Kanmani et al 2012, Guan et al 2019, Suh et al 2019 se encuentra en la naturaleza formando hidróxidos, óxidos o sulfatos, los cuales son solubles en agua.…”
Section: Introductionunclassified